Decoding germ cell tumours for clinicians. Issue 4 (July 2022) - Haider, Aiman; Verrill, Clare; Alifrangis, Constantine; Berney, Daniel Maurice
Abstract : Purpose of review: Germ-cell tumours of the testis affect predominantly younger males aged between 15 and 40 years, with nearly 74, 500 new cases estimated globally in 2020. Their rarity and the complex morphology, mean that, in nonexpert hands, there is a significant risk of misdiagnosis of both type and staging of these neoplasms. Recent findings: There have been significant changes in the 2016 WHO classification of Testicular tumours that need to be understood by both pathologists and clinicians for streamlining management. Standardised structured reporting guidelines and discussion at the multidisciplinary-team meetings lead to subsequently better health outcomes and patient safety. Summary: Therefore, communication with high-quality reports and understanding of clinicians of what constitutes an adequate report, is the key to ensure proper management of these patients. We attempt to discuss the key updates and pathological features that influence management and need to be communicated with clarity and precision.